Solution of Some Systems of Nonlinear Partial Differential Equations by Variational Iteration Method - Darvishi, Mohammad Taghi; Khani, Farzad; Hamedi-Nezhad, Somayeh (Journal of algorithms & computational technology, 2010)
This paper applies the variational iteration method to solve two systems of nonlinear partial differential equations, numerically and/or analytically. Two examples are given to illustrate the accuracy and effectiveness of the method. Comparison with Adomian decomposition method reveals that the method is easier to be implemented.